First geochronological report of tonalitic gneiss at Harvey Nunatak in western part of the Napier Complex, East Antarctica - Mami, Takehara; Kenji, Horie; Tomokazu, Hokada; Sotaro, Baba; Atsushi, Kamei; Ippei, Kitano; Prayath, Nantasin; Nugroho, Setiawan; Davaa-ochir, Dashbaatar; Yoichi, Motoyoshi (2017)
第8回極域科学シンポジウム/個別セッション：[OG] 極域地圏 12月5日（火）国立極地研究所 1階交流アトリウム The Eighth Symposium on Polar Science/Ordinary sessions: [OG] Polar Geosciences Tue. 5 Dec./Entrance Hall (1st floor), National Institute of Polar Research conference object